Uranium Isotopic Composition and Constraints on the Provenance of the Qinghai‐Tibet Plateau's Surface Dust. Issue 3 (6th March 2022) - Jiao, Xiaoyu; Dong, Zhiwen; Parteli, Eric J. R.; Brahney, Janice; Wei, Ting; Augusto, Marcelli; Nie, Junsheng; Ren, Jiawen; Qin, Xiang
Abstract: The production and emission of aeolian dust can provide key information on the contemporary and historical links between geological evolution and climate. Here we use 234 U/ 238 U isotope ratios and the uranium (U) comminution age method on samples collected from Qinghai‐Tibet Plateau (TP) surface dust and glacier snowpack/cryoconites to determine the erosion and potential transport provenance of the dust, regardless of petrological origin. The spatial variation of the ( 234 U/ 238 U) isotope ratios of TP dust showed relatively high values in the Songpan‐Ganzi‐Hoh Xil, Himalayan and the Kunlun‐Qaidam‐Qilian terranes, while showing relatively low ( 234 U/ 238 U) values in Lhasa and Qiangtang terranes, but among all samples the highest value appeared in the glaciation zone. Dust collected from nearby glacial areas with rugged terrain (e.g., the Qilian and Himalayan Mountains) have higher ( 234 U/ 238 U) values than those collected in the topologically flat non‐glacial areas. These differences are consistent with elevated erosion rates and dust comminution‐transport processes in glacial areas, which yield a major source for large quantities of fresh comminuted particles. Compared to sediments from other regions of the globe, the ( 234 U/ 238 U) values of the typical aeolian sinks (such as loess on the Loess Plateau and ice core dust, etc.) are generally lower in comparison to areas with high elevations where erosion rates are high. The ( 234 U/ 238 U) isotope values of TP dust tend to fall between the high‐elevation sites and the dust sinks, indicating the combined influence of short comminution times (tectonics, landscape dynamics, and glacial erosion) and long residence time on the TP. When compared with other central Asian dust sources, U‐Nd‐Sr isotope signatures in TP dust are distinct and can be thus used as an effective tracer of dust provenance. Using U isotopes, we show that dust originating from the TP undergoes long‐range transport and constitutes potentially significant component of the Asian and Northern Hemisphere atmospheric dust load. Plain Language Summary: This work is the first to measure the 234 U and 238 U isotopic composition of surface dust particles in the cryospheric regions of the Tibetan Plateau and to use the uranium (U) comminution age method to reveal the spatial distribution and variation of the ( 234 U/ 238 U) values and the evolution processes of Tibetan Plateau dust. In addition, we use the U isotopic composition of dust from several snowpack and cryoconite samples from glaciers in the Tibetan Plateau to constrain Tibetan Plateau dust transport distances and major sink areas. Together, the research provides new insights and understanding of Tibetan Plateau dust emissions and transport, regional tectonics, and landscape dynamics as well as the potential climate and environmental implications. Key Points: We investigated the 234 U/ 238 U isotope ratios of surface dust samples collected at various locations on the Tibetan Plateau The ( 234 U/ 238 U) isotopes reflected the influence of regional tectonic evolution, landscape dynamics, and glacier erosion processes Uranium isotopes in Tibetan Plateau dust are regionally distinguishable and thus represent a powerful tracer for dust source identification